AnalisisKebutuhan Pengembangan Handout Berbasis STEM Terhadap Pembelajaran Fisika dalam Menghadapi Era Revolusi Industri 4.0 - Yulia, Sri Rahma; Ramli, Ramli (Universitas Negeri Padang, 2019)
The era of revolution 4.0 requires superior and quality human resources. The learning of the 21st century is a form of the goal of the intellectual life of the nation. Physics is a part of natural science which is natural phenomenon. Physics is one of the subjects related to intellectual intelligence that plays a major role in supporting science and technology, so educators as facilitators in learning must be moved to be able to design and implement education that is more directed at the fostering of physics concepts that can support and be useful in everyday life. The realities in the field of physics learning approaches and the selection of teaching materials used are still not optimal. One alternative to overcome the problem is to analyze the needs of students and develop teaching materials with the STEM approach. The purpose of the study was to investigate the needs and development of STEM approach-based physical handouts. This type of research is research and development (R&D). Data collection instruments in the form of student questionnaire, learning activity questionnaire, SKL, and assessment. Based on data analysis, four analysis results can be found. First, the average value of students is still in the sufficient category so that it needs to be improved. Second, the analysis of learning activities in class obtained an average value of 67.44 in the sufficient category. Third, the SKL analysis as a reference for curriculum development obtained an average rating of 65.26 in the sufficient category. Fourth, the assessment analysis in the evaluation of learning was 82.28 in the good category. So that learning is needed in choosing the right approach and appropriate teaching materials that are very influential on the success of physics learning activities in the classroom